Research in Robot-assisted Surgery for Pheochromocytoma and Paraganglioma - OU Minjie; DENG Jianhua; ZHENG Guoyang; WEN Jin (Xiehe Yixue Zazhi)
Pheochromocytomas and paragangliomas are rare but therapeutically challenging neuroendocrine tumors in urology. Surgical treatment has been recognized as a definitive treatment. However, traditional surgical methods present certain risks and limitations. The Da Vinci robotic surgery offers a new approach for treating these tumors. This review elucidates the technical features, clinical applications, and treatment outcomes of Da Vinci robotic surgery and the progress in the treatment of pheochromocytomas and paragangliomas. In addition, this review discusses the prospects of combining Da Vinci robotic surgery with other emerging technologies, emphasizing the further research to validate its long-term efficacy and safety.